Assessing and Monitoring Student Progress in E-Learning - Svetlana V. SHELIKHOVA; Yanina I. VOYTALYANOVA (Communications of International Proceedings, 2021)
The article provides background research on different methods of assessing and monitoring the results of students' activities in the process of distance learning. As distance learning implies the usage of technical tools in educational process, the term “e-Learning” is used as a means that maintains and realizes the idea of distance learning or digital education at a remote mode. The efficient use of wide method range that e-Learning possesses is especially significant in unfavorable epidemiological situation due to the spread of a new coronavirus infection (COVID-19). The article discusses various methods and forms of assessment and criteria used for evaluation of student progress on the example of online e-Learning courses on the platform of Reshetnev Siberian State University of Science and Technology using synchronous and asynchronous techniques that can be helpful for both methodologists and teachers in their professional activities. However, findings revealed educators should pay special attention to motivating aspect, as well as time constraints and technical limitations. The efficiency of assessing methods was analyzed from subjective (students’ self-assessment) and objective (marks for the tasks) points, thus providing the material for further consideration.
Keywords: E-Learning; Distance Learning; Assessment; Evaluation Criteria